THE EFFECT OF MONOPOLY GAME AND TEACHER CREATIVITY ON CIVICS LEARNING ON EMPATHY ATTITUDES OF CLASS VD STUDENTS OF SD INPRES OESAPA KUPANG CITY - Vivi Eventi Soeki; Mintje Ratoe Oedjoe; Christine K Ekowati; Petrus Ly; Uda Geradus (Academic Journal of Educational Sciences, 2021)
This study aims to determine the effect of monopoly game media and teacher creativity on Civics learning on the empathy attitude of grade VD students of SD Inpres Oesapa, Kupang City. The subjects of this study were students of class VD SD Inpres Oesapa Kupang City, totaling 20 people. Sampling used was purposive sampling technique. Data collection tools used in this study were monopoly game media, teacher creativity and student empathy. These three variables use a Likert Scale consisting of 1 to 5 alternative answer choices, using a quantitative approach, while the analytical technique is statistical analysis with the data analysis method used is product moment correlation analysis. The results of the hypothesis test show that there is an effect based on the results of data analysis, a partial test for the Monopoly Game Media variable (X1) obtained a t-count value of 3.755 with a significance value of 0.002 0.05, then Ho is rejected and Ha is accepted, so that H1 (hypothesis 1 ) which reads "there is an influence of Monopoly Game Media on the Empathy Attitude of VD Grade Students of SD Inpres Oesapa, Kupang City is accepted". Based on the results of the partial test for the variable Teacher Creativity (X2), the t-count value is 2.317 with a significance value of 0.033 0.05, then Ho is rejected and Ha is accepted, so H2 (hypothesis 2) which reads "there is an influence on Teacher Creativity in Subjects Civics on Empathy Attitudes of Class VD Elementary School Inpres Oesapa Kupang City is accepted”. Based on the results of the F test, the calculated F is 8.565 and the significance value is 0.003 0.05, it can be concluded that Ho is rejected and Ha is accepted, so H3 (hypothesis 3) which reads "there is an influence of Monopoly Game Media and Teacher Creativity on Empathy Attitudes of Class Students The VD of SD Inpres Oesapa, Kupang city is accepted”. Based on the results of data analysis, the coefficient of determination adjusted R Square of 0.443 was obtained which was used to see the magnitude of the influence of Monopoly Game Media (X1) and Teacher Creativity (X2) on Students' Empathy Attitudes (Y). The magnitude of the coefficient of determination of 0.443 is equal to 44.3%. This figure shows that simultaneously Monopoly Game Media and Teacher Creativity contribute to the Empathy Attitude of Students by 44.3%, while the remaining 55.7% (100% - 44.3%) is influenced by other variables not proposed in this study. like other learning media, namely the game of snakes and ladders and other non-physical games. Also the basic ability to teach teachers, self-development, and an aggressive attitude, never give up.